How virtual relationality enables the incel collective, its narrative and violence - Imad Mansour; Noah Kidd (Taylor & Francis Group, 2024)
Involuntary celibates (incels) are individuals who feel alienated from society because of their perceived inability to attract women. They share a narrative which valorises violence as a means to restructure society according to misogynistic ideals. Since promoting a radical misogynistic ideology through violence is legally prohibited and socially unacceptable, it is necessary for incels to hide out online where virtual mediums promise anonymity. Virtual relationality (VR) allowed unorganised individuals with a shared grievance against mainstream societal values to develop into a secretive collective. VR means that individuals connect in chatrooms and internet forums where they exchange interpretations of a narrative which presents their social situation as oppressive and dehumanising. They blame 'modernist' values and social practices for their ills and share perspectives of how they should interact with the world. These perspectives frequently justify or condone acts of physical violence. Relating in the virtual world gave these individuals' shared grievances a sense of coherence and allowed for an amplification of the influence of their violent acts by affirming the value of extremist ideas. VR turned individuals without consistent preferences and a unifying organisational medium into a 'hydra' with a felt global presence. The virtual nature of incels complicates responses by 1) enabling the collective to have global reach, 2) allowing it to function without an organised body or institutional structures, 3) making it difficult to identify individual incels, and 4) making it difficult to tell when incels pose a genuine security threat. These realities make it crucial to develop a fuller understanding of how the incel collective functions online.